PARLIAMENTARY FUNCTIONS PORTRAYED ON EUROPEAN PARLIAMENTS' WEBSITES - Leston-Bandeira, Cristina (Revista de Sociologia e Política, 2009)
This article uses data from a pilot study on the websites of 15 parliaments in Europe to identify which parliamentary functions are portrayed on these websites. The pilot study undertook a contents analysis focused on four parliamentary functions: legislation, legitimation, representation and scrutiny, to ascertain the extent to which each of these functions is present on the websites analysed. As parliaments face difficulties of public perception, their websites become an important tool for dissemination of parliamentary work. And yet we know little about what these websites portray, when it comes to parliamentary activity. Are these websites a reflection of parliamentary work? To what extent do these websites express political debate? To what extent are these websites comprehensive to all of the roles performed by parliaments? This article shows that legislation is the main focus of parliamentary websites in Europe and representation the one that has less devoted space. This may go some way to explain why some parliamentary websites are considered as too dense and not user friendly. We also show that parliamentary websites tend to focus on parliamentary outputs to the detriment of parliamentary actors. Because of their institutional collective representation, parliaments are cautious in focusing on politicians or parties; instead they focus on what parliaments produce (laws, questions, debates, etc.). Again, this goes some way to explain why parliaments’ websites may not be as engaging as one may expect, simply because they are not meant to reflect political debate, but simply to facilitate it.